Heatmap analysis to differentiate diverse player types in table tennis—A training and tactical strategy development potential - Haas, F.; Baumgartner, T.; Klein-Soetebier, T.; Seifriz, F.; Klatt, S. (Applied Sciences, 2023)
(1) Background: Computer-based analyses have been widely used to study aspects of various team and racket sports. However, such analyses have so far eluded table tennis, except in special competition forms, under fixed laboratory conditions or have only tracked the ball. The aim was to detect a basic, global, positional behavior, independent of the score.